Answer:
Refer below.
Step-by-step explanation:
The task involves checking whether the given functions are a solution to the given differential equation.
Given differential equation:
[tex]2y'+5y=3e^{-x}[/tex]
Asummed solutions:
[tex]\text{(a) } y = e^{-x}\\\\\text{(b) } y = e^{-x}+e^{-\frac{5}{2}x}\\\\\text{(c) } y = e^{-x}+Ce^{-\frac{5}{2}x}[/tex]
[tex]\hrulefill[/tex]
Answering Part (a):[tex]\hrulefill[/tex]
For the function y = e⁻ˣ we will find the first and second derivatives of 'y':
Substitute these expressions into the differential equation:
[tex]\Longrightarrow 2\left(-e^{-x}\right)+5\left(e^{-x}\right)=3e^{-x}[/tex]
Simplify the above equation, if the L.H.S equals the R.H.S then 'y' is a solution to the differential equation:
[tex]\Longrightarrow -2e^{-x}+5e^{-x}=3e^{-x}\\\\\\\\\therefore 3e^{-x}=3e^{-x} \ \checkmark[/tex]
Thus, y = e⁻ˣ is a solution to the given differential equation.
[tex]\hrulefill[/tex]
Answering Part (b):[tex]\hrulefill[/tex]
For the function y = e⁻ˣ + e^(-5x/2) we will find the first and second derivatives of 'y':
[tex]\bullet \ y = e^{-x}+e^{-\frac{5}{2}x}\\\\\bullet \ y' = -e^{-x}-\dfrac{5}{2}e^{-\frac{5}{2}x}[/tex]
Substitute these expressions into the differential equation:
[tex]\Longrightarrow 2\left( -e^{-x}-\dfrac{5}{2}e^{-\frac{5}{2}x}\right)+5\left( e^{-x}+e^{-\frac{5}{2}x}\right)=3e^{-x}[/tex]
Simplify the above equation, if the L.H.S equals the R.H.S then 'y' is a solution to the differential equation:
[tex]\Longrightarrow -2e^{-x}-5e^{-\frac{5}{2}x}+ 5e^{-x}+5e^{-\frac{5}{2}x}=3e^{-x}[/tex]
[tex]\therefore 3e^{-x}=3e^{-x} \ \checkmark[/tex]
Thus, y = e⁻ˣ + e^(-5x/2) is a solution to the given differential equation.
[tex]\hrulefill[/tex]
Answering Part (c):[tex]\hrulefill[/tex]
For the function y = e⁻ˣ + Ce^(-5x/2) we will find the first and second derivatives of 'y':
[tex]\bullet \ y = e^{-x}+Ce^{-\frac{5}{2}x}\\\\\bullet \ y' = -e^{-x}-\bar Ce^{-\frac{5}{2}x}[/tex]
Substitute these expressions into the differential equation:
[tex]\Longrightarrow 2\left( -e^{-x}-\bar Ce^{-\frac{5}{2}x}\right)+5\left( e^{-x}+Ce^{-\frac{5}{2}x}\right)=3e^{-x}[/tex]
Simplify the above equation, if the L.H.S equals the R.H.S then 'y' is a solution to the differential equation:
[tex]\Longrightarrow -2e^{-x}- \bar Ce^{-\frac{5}{2}x}\right)+5e^{-x}+\bar Ce^{-\frac{5}{2}x}\right)=3e^{-x}[/tex]
[tex]\therefore 3e^{-x}+Ce^{-\frac{5}{2}x}=3e^{-x}[/tex]
Thus, y = e⁻ˣ + Ce^(-5x/2) may or may not be a solution to the DE, it will depend upon the value of the arbitrary constant 'C'.